Peranan Muhasabah Sebagai Upaya Dalam Menghadapi Krisis Kepercayaan Diri Remaja - Mohamad Ilham Habibie; Muhammad Dito Cahyadi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research aims to examine the role of muhasabah as an effort to deal with teenagers' self-confidence crisis. Using a literature study method, this research analyzes relevant literature to understand how muhasabah, as a form of self-introspection in Islam, can help teenagers overcome the self-doubt they often experience. Based on the three main steps presented by Ibnu Qoyyim al-Jauziyah—comparing Allah's blessings and the evil done, distinguishing between rights and obligations, and understanding the meaning of satisfaction from obedience—it was found that muhasabah can be an effective tool in strengthening self-confidence. By doing muhasabah, teenagers can recognize and overcome weaknesses, and rebuild healthy self-confidence through deep reflection and strengthening spiritual values. The research results show that muhasabah has great potential in supporting the emotional and mental development of teenagers in this modern era.